Nail gun injuries treated in U.S emergency departments, 2006–2011: Not just a worker safety issue. Issue 8 (27th April 2015) - Lipscomb, Hester J.; Schoenfisch, Ashley L.; Welch, Laura; Baker, Robin
<x xml:space="preserve">Abstract</x> Background Nail guns increase productivity in residential building but with a corresponding increase in worker injuries. They are also easily accessible, at low cost, to consumers. Methods Data from the occupational supplement to the National Electronic Injury Surveillance System (NEISS‐Work) were used to calculate national estimates of work‐related injuries from nail guns between 2006 and 2011. These were compared to estimates of consumer injuries obtained through online access to the Consumer Product Safety Commission's (CPSC) NEISS data. Results Approximately 25, 000 ED‐treated work‐related and consumer nail gun injuries were estimated each year. During the construction economy collapse, injuries among workers declined markedly, closely following patterns of reduced residential employment. Reduction in consumer injuries was much more modest. Conclusions Current nail gun injury patterns suggest marked blurring of work and home exposures. A united effort of CPSC, NIOSH, and OSHA is warranted to address these preventable injuries. Am. J. Ind. Med. 58:880–885, 2015. © 2015 Wiley Periodicals, Inc.